Investigation of Cadmium and Lead Contents in Iranian Rice Cultivated in Babol Region - Ali Zazouli, Mohammad; Mohseni Bandpei, Anoshiravan; Ebrahimi, Masoumeh; Izanloo, Hassan (Asian Journal of Chemistry, 2010)
This investigation surveyed cadmium and lead contents of Iranian rice (Oryza saliva) which is predominant rice culture in north of Iran. A total of 72 samples were collected from rice farms in Babol region of Mazandaran province. The samples were collected in during harvesting of rice in farm. Two methods was used for cooking; Kateh and Pilaw. The grains of raw polished and cooked rice were digested by acid digestion method and then were analyzed for Cd and Pb by atomic absorption spectrometry. The results showed that average content of Pb in raw polished rice was 11.5 ± 6.4 μg/g dry wt. The minimum and maximum Pb content in raw polished rice was 2.92 ± 0.8 and 20.26 ± 7.8 μg/g for Tarom Hashemi from Boleh Kola and Fajer from Meson Abad, respectively. Analysis showed that cadmium was not detectable in all rice samples. The average content of Pb in Pilaw was lower than Kateh in all samples. It is noted that the average content of Pb was found to be upper the FAO/WHO guidelines. To assess the safety of dietary of intake, weekly intake of Pb by rice was calculated based on daily consumption of rice and dietary intake compared with the Provisional Tolerable Weekly Intake (PTWI) established by the JECFA (WHO/FAO). The results indicated that weekly intake lead was less than the maximum weekly intake recommended by WHO/FAO.